Business ethics and care in organizations - Fotaki, Marianna; Islam, Gazi; Antoni, Anne (Routledge studies in business ethics ;, 2020)
"Care is a human ability we all need for growing and flourishing. It implies considering the needs and interests of others, and the quality of how we relate to each other is often defined by care. While the value of care in private life is widely recognized, its role in the public sphere is contested and subject to political debates. In work organizations, instrumentality frequently overrides considerations for colleagues and coworker's wellbeing, while relationships are often sacrificed in the service of performance and meeting organizational targets. The questions this volume attempts to address concerns the organizational conditions that make care flourish and how a caring organization functions in practice. Specifically, we examine what it means to care for each other and what enhances caring behaviors in organizations. The volume ultimately focuses on how caring relations can contribute to making organizations better places. In this perspective, care involves the recognition of, and the limitations of, work as a key aspect of personal and social identity. Because care exceeds the sphere of individual intimacy, the book will also centre on the necessity for building caring institutions through a political process that considers the needs, contributions, and prospects of many different actors. This book aims to contribute to academic discussions on care in organizations, care work, business and organizational ethics, diversity, caring leadership, wellbeing in organizations, and research ethics. Managers, consultants, policy-makers, and students will find reflections about the goodness of care in organizations, and guidance about the ethical and practical difficulties of pursuing the project of building caring organizations"--